Genetic resources of narrow-leaved lupine (Lupinus angustifolius L.) and their role in its domestication and breeding - M. A. Vishnyakova; E. V. Vlasova; G. P. Egorova (Вавиловский журнал генетики и селекции)
Narrow-leaved lupine (Lupinus angustifolius L.) is a cultivated multipurpose species with a very short history of domestication. It is used as a green manure, and for feed and food. This crop shows good prospects for use in pharmacology and as a source of fish feeds in aquaculture. However, its genetic potential for the development of productive and adaptable cultivars is far from being realized. For crop species, the genetic base of the cultivated gene pool has repeatedly been shown as being much narrower than that of the wild gene pool. Therefore, efficient utilization of a species’ genetic resources is important for the crop’s further improvement. Analyzing the information on the germplasm collections preserved in national gene banks can help perceive the worldwide diversity of L. angustifolius genetic resources and understand how they are studied and used. In this context, the data on the narrow-leaved lupine collection held by VIR are presented: its size and composition, the breeding status of accessions, methods of studying and disclosing intraspecific differentiation, the classifications used, and the comparison of this information with available data on other collections. It appeared that VIR’s collection of narrow-leaved lupine, ranking as the world’s second largest, differed significantly from others by the prevalence of advanced cultivars and breeding material in it, while wild accessions prevailed in most collections. The importance of the wild gene pool for the narrow-leaved lupine breeding in Australia, the world leader in lupine production, is highlighted. The need to get an insight into the species’ ecogeographic diversity in order to develop cultivars adaptable to certain cultivation conditions is shown. The data on the testing of VIR’s collection for main crop characters valuable for breeders are presented. Special attention is paid to the study of accessions with limited branching as a promising gene pool for cultivation in relatively northern regions of Russia. They demonstrate lower but more stable productivity, and suitability for cultivation in planting patterns, which has a number of agronomic advantages. Analyzing the work with narrow-leaved lupine genetic resources in different national gene banks over the world helps shape the prospects of further activities with VIR’s collection as the only source of promising material for domestic breeding.